Hubungan pengetahuan dengan sikap remaja tentang bahaya merokok - Fadila, Enggar; Wardiyah, Aryanti; Keswara, Umi Romayati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Perawat Kesehatan Komunitas Indonesia (IPKKI), 2025)
Background: Every year, approximately 225,700 people in Indonesia die due to smoking or other tobacco-related diseases. Smoking leads to a decrease in antibodies and causes lung cancer. Cigarettes pose major threats to various organs in the body, including the brain, mouth, throat, heart, chest, lungs, liver, stomach, kidneys, and bladder. Purpose: To determine the relationship between knowledge and attitudes of adolescents regarding the dangers of smoking at SMP Negeri 14 Bandar Lampung. Method: This research uses a quantitative approach with a cross-sectional design. The population in this study consists of 8th-grade students, with a sample of 193 respondents, using a total sampling technique. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. Results: Based on the frequency distribution of knowledge, 56.5% of respondents had good knowledge, while 43.5% had poor knowledge. Based on the frequency distribution of attitudes, 52.3% of respondents had a positive attitude, and 47.7% had a negative attitude. A p-value of 0.001 was obtained with an Odds Ratio of 116.67. Conclusion: There is a relationship between knowledge and adolescents' attitudes toward the dangers of smoking. Keywords: Adolescents; Attitude; Cigarettes; Knowledge. Pendahuluan: Setiap tahun, sekitar 225,700 orang di Indonesia meninggal akibat merokok atau penyakit lain yang terkait dengan tembakau. Merokok menyebabkan antibodi menurun, penyakit kanker paru-paru, ancaman utama rokok terhadap berbagai organ tubuh diantaranya adalah otak, mulut, tenggorokan, jantung, dada, paru-paru, hati, perut, ginjal dan kantung kemih. Tujuan: Untuk mengetahui adanya hubungan pengetahuan dengan sikap remaja tentang bahaya merokok. Metode: Penelitian ini menggunakan jenis penelitian kuantitatif. Menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah siswa kelas 8. Sampel 193 responden menggunakan teknik total sampling. Analisa data yang digunakan yaitu analisis univariate dan bivariat dengan Uji Chi- Square. Hasil: Berdasarkan distribusi frekuensi pengetahuan, 56.5% responden memiliki pengetahuan baik dan 43.5% responden memiliki pengetahuan kurang. Berdasarkan distribusi frekuensi sikap, 52.3% responden memiliki sikap positif dan 47.7% responden memiliki sikap negatif. Didapatkan p value 0.001 dengan Odds Ratio (OR) 116.67. Simpulan Ada hubungan antara pengetahuan dengan sikap remaja tentang bahaya merokok. Kata Kunci: Pengetahuan; Remaja; Rokok; Sikap.